Tracking anthropogenic influences on the continental shelf of China with sedimentary linear alkylbenzenes (LABs) - Wei, Gao-Ling; Liu, Liang-Ying; Bao, Lian-Jun; Zeng, Eddy Y. (Marine pollution bulletin, 2014)
•The entire continental shelf off China was subject to light sewage pollution.•Sedimentary LAB levels in the study region were at the low end of the global range.•Different input mechanisms contribute to LABs in different shelf sediments.•LABs are useful markers in tracking anthropogenic impacts on a large spatial scale. Surface sediments collected along the entire continental shelf of China, including Yellow Sea, the East China Sea (ECS) inner shelf and the South China Sea (SCS), were analyzed for linear alkylbenzenes (LABs), from which regional anthropogenic influences on the marine environment were assessed. The occurrence of LABs (5.6–77ng/g; mean: 25ng/g; median: 20ng/g) implied light sewage contamination in coast sediment off China. Specifically, the SCS had higher sedimentary LAB levels than Yellow Sea and the ECS inner shelf, which was mainly related to the intensity of domestic wastewater discharge and marine fishing activities. Values of L/S and C13/C12 (defined in the main text) suggested certain degradation while I/E indicated limited degradation of LABs. Also, additional input sources and congener inter-conversions may have contributed to the inconsistent results for degradation of LABs in offshore sediments. Atmospheric inputs and wastewater discharge from marine fishing vessels predominantly contributed to sedimentary LABs in Yellow Sea and the SCS, while riverine input was mainly responsible for LABs along the ECS inner shelf.